Effects of Computer-Simulated Instructional Strategy on Senior Secondary School Students’ Interest and Achievement in Practical Physics in Imo State, Nigeria (2014)
Due to the abstract nature of physics, many secondary school students have low interest and perform poorly in the subject. Literature showed that to stimulate students‟ interest, better conceptual understanding and achievement, there is the need to introduce computer-simulated experiments in physics practical classes. Previous studies on the use of computer-simulated experiments in physics practical activities have focused more on students in higher institutions than on secondary school students. This study, therefore, investigated the effects of computer-simulated instructional strategy on senior secondary school (SSS) students‟ interest and achievement in physics practicals in Imo State, Nigeria. It also determined the moderating effect of numerical reasoning ability (NRA)and perceptual reasoning ability (PRA). This study adopted a pretest-posttest, control group quasi-experimental design. Multistage random sampling was used to select 359 of intact classes of SSS II from six secondary schools from Owerri Educational Zone. Participants were randomly assigned to treatment groups: Computer-Simulated Experiment (CSE), Computer-Simulated and Hands-on Experiment (CSHE) and Conventional Hands-on Experiment (CHE). Treatment lasted eight weeks. Instruments were used: Physics Achievement Test (r =0.84), Students‟ Interest in Physics Questionnaire (r =0.85), Numerical Ability Test (r= 0.90), Perceptual Ability Test (r = 0.87), Practical Test (r = 0.84) and Software Package. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using MANCOVA. Treatment had a significant effect on students‟ achievement and interest in physics practical, (= 0.91, F (4,670) = 8.32, η2= 0.047). Also, treatment had a significant effect on students‟ achievement (F (2,336) = 14.76, p < 0.025, η2 = 0.081) but had no significant effect on interest. Students exposed to CSE performed slightly better ( ̅=38.67;SD=6.86) than those in CSHE ( ̅ = 38.56, SD = 6.85) and CHE ( ̅ = 33.37; S.D = 7.51). The NRA had asignificant effect on achievement and interest in physics practicals (= 0.96, F (4,670) =3.62, η2 = 0.021), Also, it had a significant effect on achievement, (F(2,336)=420,p<0.025,η2= 0.025) but none on interest. Students with low NRA students performed betterthan high and moderate ability students. The NRA had no effect on interest. Also, PRAhad a significant effect on students‟ achievement and interest in physics practicals (=0.95, F (4,670) = 4.84; η2 = 0. 028) as well as a significant effect on students‟ achievement (F(2,336) = 7.89, p <0.025, η2 = 0.045) but none on interest. Students with high PRA performed better ( ̅ = 38.19; S.D. = 8.62) than moderate ( ̅ = 37.56; S.D. = 6.91) and low ( ̅ = 24.49; S.D. = 6.35) abilities. There was a significant interaction effect of treatment and PRA on students‟ achievement and interest (= 0.95; F (8,670) = 2.21; η2 = 0.026). Computer-stimulated experiments enhanced students‟ conceptual understanding and achievement in physics; however, when combined with hands-on experiment, it became less effective. Therefore, curriculum planners and teachers should use the instructional strategy particularly for moderate perceptual ability and low numerical ability students.